FENOMENALOGIS KEBERADAAN ALLAH - ., Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2022)
God is life, he is the essence of life, if someone prefers, the essence of life is a god. Saying this we already know what God is, we know it is not through the impact of knowledge or learning, we do not know it through the mind, against the background the truth of the world, instead we know it, and can know it, only in and through life itself, we can know the essence of God only in God.This life is not a biological life that is defined by objective and external characteristics, or abstract and philosophical , but it is an absolutely phenomenal life, a radically immanent life that has the power to show itself in itself without distance, a life that expresses itself permanently. One's manifestation of oneself and self-revelation that does not consist of the reality of seeing one's outside or understanding the outside world, but in fact feelings and feelings of oneself, experiencing within oneself have inner and affective realities. As Michel Henry said in this same book,